2021
DOI: 10.3390/cancers13236059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of HER2-Low Expression in Non-Metastatic Triple-Negative Breast Cancer and Correlation with Other Biomarkers

Abstract: HER2-low breast cancer (i.e., HER 1+ or 2+, without gene amplification) is an emerging subtype for which very few data are available, especially within the triple-negative breast cancer (TNBC) group. Our aim was to evaluate HER2 expression and its prognostic value in a large retrospective series of patients with non-metastatic TNBC (median age: 57.7 years; range: 28.5–98.6). Among the 296 TNBC samples, 83.8% were HER2 0, 13.5% were HER2 1+, and 2.7% were HER2 2+ (HercepTestTM and 2018 ASCO/CAP guidelines for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 32 publications
8
59
3
Order By: Relevance
“…Previous literature is inconsistent with respect to outcome. In line with our findings, various studies reported no difference in overall survival www.nature.com/scientificreports/ between HER2-and HER2low breast cancer patients 5,15,29 . Denkert et al reported that ER+/HER2low breast cancers have a lower pathological complete response rate after neoadjuvant chemotherapy compared to ER+/ HER2-cancers 14 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous literature is inconsistent with respect to outcome. In line with our findings, various studies reported no difference in overall survival www.nature.com/scientificreports/ between HER2-and HER2low breast cancer patients 5,15,29 . Denkert et al reported that ER+/HER2low breast cancers have a lower pathological complete response rate after neoadjuvant chemotherapy compared to ER+/ HER2-cancers 14 .…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, while patients with HR-positive had a similar DFS regardless the expression of HER2, those with HR-negative has a worse outcome when HER2 was low instead of zero (Supplementary Figure S1). Our finding is in line with the recently reported analysis of triple negative breast cancer cases outcome with respect to HER2 expression which found a worse relapse-free survival among HER2-low than HER2-0 cases (Jacot et al, 2021;U.S. National Library of Medicine, 2022).…”
Section: Figuresupporting
confidence: 92%
“…93 It is interesting to note that triplenegative HER2-low cancers were associated with lower grade and the AR(+)FOXA1(+) phenotype, features associated with the LAR subtype. 94 This clincopathological association could have a therapeutic implication for the anti-HER2 ADC in TNBC.…”
Section: A N T I B O D Y -D R U G C O N J U G a T E Smentioning
confidence: 93%